2002
DOI: 10.1590/s1415-47572002000300017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among Arachis species based on AFLP

Abstract: Amplified Fragment Length Polymorphism (AFLP) was used to establish the genetic relationships among 20 species from seven of the nine sections of genus Arachis. The level of polymorphism among nine accessions of the cultivated peanut, A. hypogaea L., was also evaluated. Three combinations of primers were used to amplify the AFLPs. The fragments were separated in 6% denaturing acrylamide gels. A total of 408 fragments were analyzed. An average of 135.3 fragments per primer combination were scored, and the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
5
30
0
5
Order By: Relevance
“…Relationships between and within closely related genera were also examined with the AFLP method (Vos et al 1995) that is increasingly applied to assess genetic similarity at the interspecific level (e.g., Aggarwal et al 1999;Mace et al 1999;Gimenes et al 2002;Beardsley et al 2003;Després et al 2003). Within Bromelioideae, our special interest is in Aechmea and related genera and in the smaller genera forming the southwestern limit of the family distribution (Ochagavia, Fascicularia, and Greigia).…”
Section: Authors Molecular Datamentioning
confidence: 99%
“…Relationships between and within closely related genera were also examined with the AFLP method (Vos et al 1995) that is increasingly applied to assess genetic similarity at the interspecific level (e.g., Aggarwal et al 1999;Mace et al 1999;Gimenes et al 2002;Beardsley et al 2003;Després et al 2003). Within Bromelioideae, our special interest is in Aechmea and related genera and in the smaller genera forming the southwestern limit of the family distribution (Ochagavia, Fascicularia, and Greigia).…”
Section: Authors Molecular Datamentioning
confidence: 99%
“…A variety of molecular markers have been used to characterize the genetic diversity in groundnut, e.g. RFLPs (Halward et al 1991), RAPDs (Dwivedi et al 2001;Subramanian et al 2000), and AFLPs Prakash 1997, 2001;Gimenes et al 2002). All these studies have reported low levels of polymorphism within the cultivated gene pool.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites (SSRs) as DNA markers are highly polymorphic, highly abundant, show co-dominant inheritance, analytically simple and readily transferable between different plant species (He et al 2003). Previous studies showed that SSR markers could detect more polymorphism in peanut than other molecular markers like RFLPs (Gimenes et al 2007), AFLPs (He and Prakash, 2001;Gimenes et al 2002) and RAPDs (Dwivedi et al 2001;Subramanian et al 2000).…”
mentioning
confidence: 98%